2014
DOI: 10.1111/mmi.12770
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Mycobacterium tuberculosis type VII secretion system chaperone EspG5 in complex with PE25–PPE41 dimer

Abstract: Summary The growth or virulence of Mycobacterium tuberculosis bacilli depends on homologous type VII secretion systems, ESX-1, ESX-3 and ESX-5, which export a number of protein effectors across membranes to the bacterial surface and environment. PE and PPE proteins represent two large families of highly polymorphic proteins that are secreted by these ESX systems. Recently, it was shown that these proteins require system-specific cytoplasmic chaperones for secretion. Here, we report the crystal structure of M. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
135
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(154 citation statements)
references
References 57 publications
(93 reference statements)
13
135
0
Order By: Relevance
“…The different quaternary structures of EspG chaperones reflect the variability that exists within this protein family ( Table 2). As previously proposed [26], EspG likely acts as a chaperone that maintains PE/PPE secretion targets in the cytosol in a soluble state. To allow this, the PE-PPE interaction interface of EspG proteins must be available for effector binding.…”
Section: Variation Of Quaternary Structure Within Espg Protein Familymentioning
confidence: 88%
See 3 more Smart Citations
“…The different quaternary structures of EspG chaperones reflect the variability that exists within this protein family ( Table 2). As previously proposed [26], EspG likely acts as a chaperone that maintains PE/PPE secretion targets in the cytosol in a soluble state. To allow this, the PE-PPE interaction interface of EspG proteins must be available for effector binding.…”
Section: Variation Of Quaternary Structure Within Espg Protein Familymentioning
confidence: 88%
“…In the PE25-PPE41-EspG 5mtu structure (PDB ID 4KXR [26] observed in the PE25-PPE41-EspG 5 structure.…”
Section: The Espg Fold Is Conserved In Esx-1 Esx-3 and Esx-5 Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that all ESX-dependent proteins do not belong to the PPE protein family, such as the ESX-5-dependent EsxN substrate [236]. It was also shown that cytosolic chaperones specifically interact with the ESX substrate, such as EspG, with various PE/PPE complexes [237,238]. The ESX system has since been called the type VII secretion system (T7SS) and is made of a small number of mostly IM proteins, EccB-E, and some cytoplasmic proteins, EccA and Esx [239].…”
Section: Type VII Secretion Systemmentioning
confidence: 96%